The characterisations of airborne particulates soiling defect towards museum artefacts - Mohd. Din, Shamzani Affendy; Mat Husin, Nur Baiti; Othman, Rashidi (American Scientific Publishers, 2017)
The conservation of museum artefact and its preservation against possible damage from air pollution is of increasing concern. Soiling is harmful to the inorganic artefact as it happened when the airborne particulates deposited onto the surface of objects and then the chemical compounds catalyse the oxidation of sulphur dioxide (SO2) to form sulfuric acid which presence as the black crust. The deposited airborne material can attack museum collections chemically. Therefore, museum environment should have low particle concentrations. This paper present current literature studies on the relationship of chemical characteristics of airborne particulates with the soiling defect of the inorganic artefact. The aim of this article is to provide a better understanding of the origin of particulates pollutants within the built environment. This research employs a qualitative method which encompasses the technique of case studies and content analysis of reports on physical and chemical properties of airborne particulates and soiling defect of museum artefact. A significant finding of this paper is the in-depth understanding of the various chemical characterization of airborne particulate that reacts with the artefact surface to form a black crust or soiling defect. The results will assist future research to come up with a variety of solution and techniques to control the rate of particle depositing to the surfaces of an artefact as many of the techniques are cost saving. So, to protect and conserve the relics of human history, it is important to apprehend the interaction of atmospheric pollutants, airborne particulates and heritage material towards the conservation of built environment.